Approach to Acute Cardiovascular Complications in COVID-19 Infection. (July 2020) - Ranard, Lauren S.; Fried, Justin A.; Abdalla, Marwah; Anstey, D. Edmund; Givens, Raymond C.; Kumaraiah, Deepa; Kodali, Susheel K.; Takeda, Koji; Karmpaliotis, Dimitrios; Rabbani, LeRoy E.; Sayer, Gabriel; Kirtane, Ajay J.; et al.
Abstract : The novel coronavirus disease 2019, otherwise known as COVID-19, is a global pandemic with primary respiratory manifestations in those who are symptomatic. It has spread to >187 countries with a rapidly growing number of affected patients. Underlying cardiovascular disease is associated with more severe manifestations of COVID-19 and higher rates of mortality. COVID-19 can have both primary (arrhythmias, myocardial infarction, and myocarditis) and secondary (myocardial injury/biomarker elevation and heart failure) cardiac involvement. In severe cases, profound circulatory failure can result. This review discusses the presentation and management of patients with severe cardiac complications of COVID-19 disease, with an emphasis on a Heart-Lung team approach in patient management. Furthermore, it focuses on the use of and indications for acute mechanical circulatory support in cardiogenic and/or mixed shock.